Trialling critical reflection in education: the benefits for school leaders and teachers. Issue 4 (4th July 2021) - Baxter, Lindy P.; Southall, Anne E.; Gardner, Fiona
ABSTRACT: This study explores the experience of leaders and teachers in two Australian primary schools who were seeking more effective ways to respond to students with challenging behaviours and improve their classroom climates. The schools implemented a form of critical reflection as a strategy to understand their experiences, beliefs and practices within the social and cultural context of a school. School leaders and teachers adopted the Reflective Circle Education Model, a group process of reflective circles to explore their reactions to specific school experiences in order to generate new practices that might bring classroom change. After six reflective circles, staff were interviewed and they reported increased mutual support and validation from peers, and a deeper understanding of the values and assumptions that influenced their actions and reactions. As a result, staff also reported reduced stress and improved classroom climates.